2018
DOI: 10.3390/en11061445
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Technical Aspects of Flexible Storage Photovoltaic Systems in Europe

Abstract: Solar energy has an increasing role in the global energy mix. The need for flexible storage photovoltaic systems and energy storage in electricity networks is becoming increasingly important as more generating capacity uses solar and wind energy. This paper is a study on the economic questions related to flexible storage photovoltaic systems of household size in 2018. The aim is to clarify whether it is possible in the European Union to achieve a payback of the costs of flexible storage photovoltaic system inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 30 publications
1
49
0
2
Order By: Relevance
“…Figure 3 shows the power flows to the load from the utility grid, coupled with the PV and the energy storage system. The equipment and materials used for the flexible storage system include: PV modules, PV-inverters, a battery-inverter, a battery, a frame on the roof, cables, and outlets [28]. Solar PV modules consist of an assembly of solar PV cells, which convert the solar energy into direct current (DC) through the photovoltaic effect.…”
Section: Methodological Detailmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows the power flows to the load from the utility grid, coupled with the PV and the energy storage system. The equipment and materials used for the flexible storage system include: PV modules, PV-inverters, a battery-inverter, a battery, a frame on the roof, cables, and outlets [28]. Solar PV modules consist of an assembly of solar PV cells, which convert the solar energy into direct current (DC) through the photovoltaic effect.…”
Section: Methodological Detailmentioning
confidence: 99%
“…To overcome this drawback, a hybrid system is utilized, which consists of solar PV and a dual energy storage system connected with load [26,27]. The installation of the hybrid PV and energy storage system is economically feasible to meet the consumer load demand, as more generating capacity uses solar and wind energy [28]. Nizetic et al [29], investigated the design and performance of the hybrid system for different operating conditions, with the conclusion that the hybrid system can be a cost-effective solution for small-and medium-scale applications.…”
Section: Energy Storage and Its Effective Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Levelized Cost of Electricity (LCOE) estimated for CSP is still high as compared to the other renewable technologies, as shown in Table 2 [55,[63][64][65][66].…”
Section: The Concept Of Concentrated Solar Power (Csp)mentioning
confidence: 99%
“…Strong solar radiation [17], low energy technology costs [18], and accurate forecasting capacity [19] can effectively guarantee the financing of photovoltaic projects and the operation and maintenance after production. Garcia-Alvarez found that compared with the tariff scale and contract period, the on-grid tariff policy has a significant impact on photovoltaic power generation [20], and policymakers should make special modifications to grid tariffs and electricity prices to help excellent PV systems enter the market [21]. The research by Ding showed that residents in different regions have different expectations for photovoltaic power generation facilities.…”
Section: Introductionmentioning
confidence: 99%